Two new species of mealybugs from Patagonia, Argentina (Coccoidea: Pseudococcidae) - Granara, Maria Cristina (2004)
Two new species of mealybugs, Eurycoccus chubutensis and Pseudanonina vernacula, have been discovered in the Patagonia Region of Argentina, collected on Nothofagus dombeyi and on grass, probably Stipa so. Adult females and available inmature stages of each species are described and iustrated and are compared with other mealybugs from the area.